Evaluation of agricultural land carrying capacity and projection of agricultural land requirements in Grobogan Regency based on Geographic Information Systems (GIS) - Muhammad Fauzan; Mochamad Arief Budihardjo; Budi Prasetyo Samadikun (University of Islam Malang, 2026)
Increasing population growth and agricultural land conversion pose significant challenges to food security, particularly in regions heavily dependent on agriculture. Grobogan Regency, a major rice-producing area in Central Java, has experienced a decline in harvested area alongside rising population pressure, indicating potential risks to long-term agricultural sustainability. Unlike previous studies that examine land carrying capacity, land requirements, or land use change separately, this study integrates these aspects within a Geographic Information System (GIS)-based spatial framework. The novelty of this study lies in integrating agricultural land carrying capacity, land-use requirement projections, and GIS-based land-use analysis within a multi-temporal, spatially explicit framework at the sub-district level to provide a more comprehensive understanding of agricultural sustainability and land-based food supply planning under population pressure. This study employed a quantitative, descriptive approach, combined with GIS-based spatial analysis, using secondary data on population, harvested area, rice production, and land use for 2014, 2019, and 2024. Agricultural land carrying capacity was calculated using the Suhardjo–Tukiran method, while land requirements were projected using a geometric population growth model. The results show that carrying capacity remained positive, with σ values of 3.45 in 2014, 4.62 in 2019, and 3.94 in 2024, although the number of Class I sub-districts declined from 18 in 2019 to 16 in 2024, indicating increasing localized land pressure and spatial disparities in agricultural resources. Projected land requirements increased from 46,699.19 ha in 2029 to 49,297.08 ha in 2034, while land-use analysis indicates ongoing changes in agricultural and non-agricultural land allocation. These findings highlight the importance of GIS-based spatial planning and land-use control to support sustainable agricultural development and long-term food security.